Folate deprivation induces cell cycle arrest at G0/G1 phase and apoptosis in hippocampal neuron cells through down-regulation of IGF-1 signaling pathway. (October 2016) - Yang, Yang; Li, Xi; Sun, Qinwei; He, Bin; Jia, Yimin; Cai, Demin; Zhao, Ruqian
Abstract: Folate deficiency contributes to impaired adult hippocampal neurogenesis, yet the mechanisms remain unclear. Here we use HT-22 hippocampal neuron cells as model to investigate the effect of folate deprivation (FD) on cell proliferation and apoptosis, and to elucidate the underlying mechanism. FD caused cell cycle arrest at G0/G1 phase and increased the rate of apoptosis, which was associated with disrupted expression of folate transport and methyl transfer genes. FOLR1 and SLC46A1 were ( P  < 0.01) down-regulated, while SLC19A1 was up-regulated ( P  < 0.01) in FD group. FD cells exhibited significantly ( P  < 0.05) higher protein content of BHMT, MAT2b and DNMT3a, as well as increased SAM/SAH concentrations and global DNA hypermethylation. The expression of the total and all the 3 classes of IGF-1 mRNA variants was significantly ( P  < 0.01) down-regulated and IGF-1 concentration was decreased ( P  < 0.05) in the culture media. IGF-1 signaling pathway was also compromised with diminished activation ( P  < 0.05) of STAT3, AKT and mTOR. CpG hypermethylation was detected in the promoter regions of IGF-1 and FOLR1 genes, while higher SLC19A1 mRNA corresponded to hypomethylation of its promoter. IGF-1 supplementation in FD media significantly abolished FD-induced decrease in cell viability. However, IGF-1 had limited effect in rescuing the cell phenotype when added 24 h after FD. Taken together, down-regulation of IGF-1 expression and signaling is involved in FD-induced cell cycle arrest and apoptosis in HT-22 hippocampal neuron cells, which is associated with an abnormal activation of methyl transfer pathway and hypermethylation of IGF-1 gene promoter.